Reduction tuning of ultrathin carbon shell armor covering IrP2 for accelerated hydrogen evolution kinetics with Pt-like performance. Issue 4 (5th January 2021) - Yu, Wen-Li; Chi, Jing-Qi; Dong, Bin
Abstract : Developing highly durable electrocatalysts for hydrogen evolution via water splitting over a wide pH range has become increasingly necessary for renewable energy systems. Abstract : Developing highly durable electrocatalysts for hydrogen evolution via water splitting over a wide pH range has become increasingly necessary for renewable energy systems. Ideally carbon is employed as a support to improve the electrical contact of the active sites, and simultaneously acts as protective carbon layers for the core to improve the durability of the catalyst. Herein, a phosphating strategy is described, in which the IrP2 core encapsulated in N, P co-doped carbon nanoshells (IrP2 @NPC) with a tunable thickness of carbon shells for Pt-like HER activity over a wide pH range is obtained. In this phosphating process, P-rich IrP2 @NPC with a controlled P content is responsible for tuning the thickness of the carbon shells and optimizing the electronic configuration of the metallic Ir, and thus synergistically accelerating the hydrogen evolution kinetics of electrocatalyst. The as-obtained IrP2 @NPC nanoshells with optimized carbon thickness can not only possess Pt-like activity for HER with low overpotentials of only 32, 42, and 90 mV to drive a current density of 10 mA cm −2 in 0.5 M H2 SO4, 1.0 M KOH, and 1.0 M PBS, respectively, but also exhibit superior long-term durability compared to Pt/C, over a wide pH range. So, this paper presents a potential strategy for designing carbon-based transition metal phosphides with the high catalytic activity and durability desired for HER and beyond.